A model of agricultural sustainable added value chain: The case of the Dominican Republic value chain - Gómez-Luciano, Cristino Alberto (2019)
The aim of this paper is to develop a model of sustainable added value chain (SAVC). The model i) considers consumers expectations, ii) analyses the determinant producers´ factors to perform the SAVC and iii) ranks the agricultural subsectors according the SAVC. The value chain methodology was used to assess the sustainability of the agricultural value chain and develop the model. The model was tested in the Dominican Republic’s agricultural value chain. The results showed i) producers´ access to SAVC depends on the subsector, location and resources, ii) organic banana and avocado are the subsectors with the best potential SAVC while sweet potatoes and rice have the lowest potential and iii) producers are in an early stage to adopt the consumers´ expectations endangering SAVC. Using mixed methods to investigate the SAVC this paper provides an approach that reflects the complex and iterative nature of a real supply chains and can be used by researchers, policymakers and practitioners to better understand and describe decision making and to develop informed policies and interventions beyond SAVC. This research challenges the innate complexity of local supply chains and the presence of barriers for SAVC.